TINGKAT PEMAHAMAN OPERATOR SEKOLAH DASAR NEGERI PADA APLIKASI DAPODIK DI KECAMATAN GELUMBANG - Prihatini, Deslina; Emilia, Emilia; Yuhanis, Yuhanis (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The background of this study begins with the role of school operators which is very important in compiling databases or inputting Basic Education Data (Dapodik) in schools. This study aims to determine the level of understanding of state elementary school operators in dapodik applications in Gelumbang District. In this study researchers used qualitative methods. The variable in this study is the level of understanding of school operators on the Dapodik application. Data collection techniques using interview techniques, questionnaires and documentation. The focus of the research was operators at the State Elementary School in Gelumbang District, which numbered 29 people. In general the results of this study can be concluded that the operator's understanding of Dapodik data input is good. Based on the data analysis of the existing problems, the percentage level of understanding of school operators is the number who answered SP (Very Understanding) a number of 38% of 10 statements, the number who answered P (understand) a number of 51.7% of the 10 statements, the number who answered CP (quite understand) a number of 10.3% of the 10 statements, and the number that answers KP (Less Understanding) is 0% of the 10 questions. From the results of the percentage it can be concluded that the highest percentage can be seen in the questionnaire answers understand with 52%, it is concluded that the level of understanding of the school operator is Good or already understand the duties and obligations of Dapodik operators.